2021
DOI: 10.3389/fpubh.2021.708907
|View full text |Cite
|
Sign up to set email alerts
|

Rapid COVID-19 Antigen Testing in Croatia: Risk Perception Plays an Important Role in the Epidemic Control

Abstract: Aim: To explore the clinical presentation and epidemiological history of the subjects who underwent SARS-CoV-2 antigen testing.Methods: We included 1,000 consecutive subjects who presented themselves at the diagnostic clinic in Croatia and analyzed their symptoms and epidemiological history. All subjects were classified into three groups, according to their reason of arrival; symptomatic, contacts of confirmed patients, and those who were tested due to administrative reasons.Results: On average, there were 24%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, no monitoring system could estimate the current adherence to the protective measures in real-time. Interestingly, one study showed that behavioral factors and risk perception play a role in individual risk estimation (16), suggesting that epidemiological history remains an essential tool in the epidemic monitoring and control. The overall epidemic data may strongly depend on the testing approach and capacity (17), which can generate further modeling difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no monitoring system could estimate the current adherence to the protective measures in real-time. Interestingly, one study showed that behavioral factors and risk perception play a role in individual risk estimation (16), suggesting that epidemiological history remains an essential tool in the epidemic monitoring and control. The overall epidemic data may strongly depend on the testing approach and capacity (17), which can generate further modeling difficulties.…”
Section: Discussionmentioning
confidence: 99%